Characterization of Phytophthora infestans populations in northwestern Algeria during 2008–2014. Issue 5 (May 2017) - Rekad, Fatma Zohra; Cooke, David Edward Llewelyn; Puglisi, Ivana; Randall, Eva; Guenaoui, Yamina; Bouznad, Zouaoui; Evoli, Maria; Pane, Antonella; Schena, Leonardo; Magnano di San Lio, Gaetano; Cacciola, Santa Olga
Abstract: A total of 161 Phytophthora infestans isolates, collected from infected potato and tomato plants during 2008–2014, were characterized based on mating type, metalaxyl sensitivity and polymorphism at 12 simple sequence repeat (SSR) loci, in order to investigate the population of P. infestans in the north-west of Algeria, an emerging potato production region. The majority of isolates were of A2 mating type (112 isolates). A high percentage (89 %) of resistance to metalaxyl among isolates was detected. The metalaxyl resistant phenotype was present in both mating types with a higher percentage in A2 mating type isolates. SSR-based genotypic analysis of P. infestans population showed a low diversity. Genotype 13_A2 was the predominant in the population with a frequency of 67 % followed by 2_A1 (21 %) and 23_A1 (5 %). Genotype 23_A1 was detected only in tomato and potato isolates collected in 2013 and 2014.